Horizontal inequality and grievances: A lethal combination? A case study analyzing the impact of the Israeli settlement policy on the level of violence of Palestinian citizens living in Hebron - Dana Butler (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
This study assesses how horizontal inequalities between Israeli settlers and Palestinians living in the West Bank cause grievances among Palestinians transforming to violence towards the Israeli citizens. A scoring model tailored to Hebron's case is introduced to evaluate the line of argumentation by estimating the level of violence in the designated area. This method is based on expert interviews containing pre-surveys and a theoretical review. In a second step, the estimated level of violence is tested through data of Palestinian attacks against Israelis based on the Global Terrorism Database (1976-2018). A historical review of the Israeli settlement policy since 1967 substantiates the research. The results suggest that the applied mechanism of horizontal inequalities increases Palestinian grievances and encourages violence in Hebron. Thus, this work strengthens theoretical research of horizontal inequalities, grievances, and violence and offers a new (bottom-up) direction in the Israeli-Palestinian peace process.
Keywords: F5; F51; N45; 330; Horizontal Inequality; Grievances; Conflict; Scoring Model; Israeli Settlement Policy; West Bank; Hebron